Sewa Guna Usaha Strategi Keuangan Bisnis Pariwisata Saat Pandemi - Hery Susanto; I Nyoman Nugraha Ardana Putra (Universitas Mataram, 2022)
Tourism is the sector down when is its time fixed corona pandemic virus (disease covid-19). This study aims to lease a construction model in business between the lessor and the lessee soil used in the pandemic. An approach used is the qualitative study of cases study design or one case by observation of several different places. His case is other; although observed every year, he added that the focus observation so far is only one case. The data collection technique used is the land owner's lessor (interview), a tenant land, and the lessee, which conducts work relating to leasing business tourism in North Lombok Regency, by triangulation. The analysis method the data used as a method of Miles and Huberman. Research results show that leasing can be a strategy for the decline of the tourism sector due to the economic recession, which is the impact of the COVID-19 pandemic.